Iniciativas de paz en Colombia (2010)
This paper reviews representative literature on peace initiatives in Colombia developed; proposing a typology of interpretation of them which complements previous investigations. This proposal features two levels of initiatives: the national and community; each of these levels is correspondingly divided into four different items. This categorization is based on the variations of impact of these initiatives; in two senses: one; its influence on the dynamics and problems of the communities involved in the conflict; and two; political views and projections of their actions regarding the construction of peace and democracy in the country; in this context highlights community initiatives as the most significant.